The Use of Negative Politeness Strategies in Casual Conversation Among the Graduate Program Students - Sulistiyaningsih, Eka Fanti; Mujiyanto, Januarius; Widhiyanto, Widhiyanto (English Education Journal, 2021)
A conversation is considered as the center of human interaction. People used politeness strategies to minimize and avoid conflict that may occur in conversation. The phenomena showed that the graduate students spontaneously did their conversation with their friends who have different cultures did not realize that they used negative politeness strategies. This study aims to explain the use of negative politeness strategies in casual conversation among the English Education Department's graduate program students. The participants of this study were fourteen students of the graduate program of the English Education Department. Descriptive qualitative research with interpretative data analysis was employed in the present study. The results showed that the students used negative politeness strategy, which consists of; be conventionally indirect, question and hedge, be pessimistic, minimize the imposition, apologize, impersonalize the speaker and the hearer, state the FTA as a general rule, and go on record as incurring debt or as not indebting the hearer. It can be concluded that the study found eight sub-strategies out of ten sub-strategies of negative politeness. It has benefits for the students to improve their knowledge, especially in using negative politeness strategies.